2019
DOI: 10.17681/hsp.454678
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Academicians Perceptions of Spirituality and Spiritual Care and Their Competence in Spiritual Care

Abstract: Bu çalışmanın amacı hemşire akademisyenlerin maneviyat / manevi bakım algıları ve manevi bakım yeterliliklerini saptamak ve arasındaki ilişkiyi belirlemektir. Gereç ve Yöntem: Tanımlayıcı ve ilişkisel tipteki araştırma Haziran -Eylül 2017 tarihleri arasında gerçekleştirildi. Araştırmanın örneklemine dört üniversiteden 202 akademisyen alındı. Verilerin toplanması için hemşire akademisyenleri tanıtıcı bilgi formu, Maneviyat Ve Manevi Bakım Dereceleme Ölçeği ve Manevi Bakım Yeterlilik Ölçeği kullanıldı. Verilerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…When the mean subscale scores were examined, the highest score was for spirituality and spiritual care and the lowest score was for religiosity. The mean SSCRS scores in our study are similar to those reported in other studies of nursing students (Cruz et al, 2017; Daghan, 2018; İnce & Akhan, 2017; Kalkim et al, 2017; Tüzer et al, 2020; Wu et al, 2012). As the maximum possible SSCRS score is 5, it can be said that the students in our study have good perspectives on spirituality and spiritual care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When the mean subscale scores were examined, the highest score was for spirituality and spiritual care and the lowest score was for religiosity. The mean SSCRS scores in our study are similar to those reported in other studies of nursing students (Cruz et al, 2017; Daghan, 2018; İnce & Akhan, 2017; Kalkim et al, 2017; Tüzer et al, 2020; Wu et al, 2012). As the maximum possible SSCRS score is 5, it can be said that the students in our study have good perspectives on spirituality and spiritual care.…”
Section: Discussionsupporting
confidence: 91%
“…The content of nursing education should be comprehensive enough to enable student nurses to define spiritual care, know what spiritual care entails, and to understand the impact of nurses providing spiritual care to patients and their families (Kroning & Deborah, 2017). However, the impact on spirituality and spiritual care behaviors may not be seen due to a low ratio of lecturers to students in the university where the study was conducted, lack of sufficient knowledge of the subject among faculty members, prioritization of physical problems, and an insufficient clinical environment (Kalkim et al, 2017). Addressing the subject of spirituality in nursing education is seen as an opportunity to enhance the quality of nursing care and improve students' spiritual development and spiritual care skills (Caldeira et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, the nurses should be aware of the significance of the spiritual care. In the literature (Chandramohan and Bhagwan, 2016;Kalkım et al,2019;Tuzer et al, 2020) the nurses were not sufficiently trained about the spiritual needs of the patients during their professional education and that they lacked the necessary qualification in terms of spiritual care in designating the appropriate nursing care plan. While spiritual care has been emphasized in nursing, particularly in psychiatric nursing, it has also been established that spiritual care is a challenging task which calls for a good deal of knowledge and experience.…”
Section: The Concept Of Spirituality In Nursingmentioning
confidence: 99%